Scoping Review: WhatsApp-based Education to Increase Iron Intake to Prevent Pregnancy Anemia - Herinawati, Herinawati; Margawati, Ani; Nugraheni, Sri Achadi; Pudjonarko, Dwi (Poltekkes Kemenkes Palu, 2025)
Background: Pregnancy anemia is a global health problem that affects both mother and fetus. One solution to address pregnancy anemia is to increase iron intake, which can be done through various educational methods, including the use of technology platforms such as WhatsApp. This scoping review explores the academic literature on WhatsApp-based education to increase iron intake to prevent pregnancy anemia. Methods: This review used a scoping review method based on the Arksey and O'Malley framework. The literature search was conducted through several electronic databases, namely Google Scholar and PubMed by determining keywords using the PICO format, namely P (pregnancy anemia), I (WhatsApp), C (nil), O (iron supplementation) which captured articles from national and international journals, in English and Indonesian, using the PRISMA Method. Studies were selected from 2014-2024. Found in the initial search as many as 3427 articles and filtered to get 9 articles to synthesize. Results: The results of the article review obtained seven articles. The results showed that technology-based interventions, especially mobile applications and WhatsApp, were effective in improving the health of pregnant women through increased knowledge, anemia prevention practices, hemoglobin levels, and compliance with iron and folic acid consumption. Conclusion: WhatsApp-based education is effective in improving knowledge and anemia prevention practices among pregnant women.